2021
DOI: 10.7150/jca.51049
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group box 1 regulates gastric cancer cell proliferation and migration via RAGE-mTOR/ERK feedback loop

Abstract: Gastric cancer (GC) is a common malignancy tumour in China. Despite various therapeutic approaches to improve the survival rate of GC patients, the effectiveness of currently available treatments remains unsatisfactory. High mobility group box 1 (HMGB1) is reported to play a role in tumour development. However, the molecular mechanisms involved in HMGB1-mediated regulation of proliferation and migration of GC cells remain unclear. In the present study, we demonstrated that HMGB1 is highly expressed in GC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…CDK4 and CDK6 are of great significance to allow cell cycle progression from G1 phase into S phase ( Crozier et al., 2022 ). Besides, HMGB1 was reported to activate ERK signaling pathway and regulate tumor cell proliferation via RAGE in gastric cancer and colorectal cancer ( Tang et al., 2021 ; Huang et al., 2018 ). Hence, we speculated that RAGE-dependent ERK signaling pathway may be involved in the regulation of HMGB1 on GSC proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CDK4 and CDK6 are of great significance to allow cell cycle progression from G1 phase into S phase ( Crozier et al., 2022 ). Besides, HMGB1 was reported to activate ERK signaling pathway and regulate tumor cell proliferation via RAGE in gastric cancer and colorectal cancer ( Tang et al., 2021 ; Huang et al., 2018 ). Hence, we speculated that RAGE-dependent ERK signaling pathway may be involved in the regulation of HMGB1 on GSC proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…The engagement of RAGE and its ligands triggers signaling pathway cascade including ERK, PI3K/AKT, and Jak/STAT pathways ( Oh et al., 2018 ; Kang et al., 2014b ; Taneja et al., 2021 ). ERK binds intracellularly to the cytoplasmic domain of RAGE ( Ishihara et al., 2003 ), integrating external signals into signaling events promoting cell growth and proliferation in many cell types including glioma cells ( Huang et al., 2018 ; Tang et al., 2021 ; Wang et al., 2019 ). Furthermore, ERK1/2 phosphorylation causes a cascade activation of signaling molecules related to cell cycle, contributing to excessive tumor cell proliferation ( Ebisuya et al., 2005 ; Marshall, 1995 ; Dent, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of extracellular rhHMGB1 (200 ng/mL) also promoted migration and invasion, and these effects were attenuated by the addition of rTM (100 ng/mL) ( Figure 1 b,c). Extracellular HMGB1 transduces cellular signals by interacting with the RAGE/Erk/NF-κB pathway and contributes to stimulating the cell proliferation and migration abilities of GC cells [ 13 , 34 , 35 , 36 ]. Alterations in this pathway by extracellular rhHMGB1 and rTM were examined using Western blotting (WB).…”
Section: Resultsmentioning
confidence: 99%
“…As for TLR2, it has been reported to promote tumor growth in breast cancer and colon cancer [ 41 , 42 ]. However, the TLR-mediated tumor-promoting effects of HMGB1 in gastric cancer have been negative, and the HMB1-RAGE-signaling pathway has been reported as the main tumor-promoting factor [ 21 , 25 , 36 , 43 ]. The present results also revealed the increased phosphorylation of Erk and NF-κB and the activation of the RAGE/Erk/NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Since, researchers have proposed many mechanisms to explain the involvement of HMGB1 in GC proliferation and metastasis, such as the HMGB1-mediated PI3K/Akt/HIF-1α signaling pathway ( 162 ) and activation of the MEK/ERK or NF-κB signaling pathway to induce GC cell proliferation through interactions with RAGE ( 163 , 164 ). Moreover, HMGB1 can also enhance the expression of cyclins, thereby inducing epithelial–mesenchymal transition and matrix metalloproteinase (MMP) expression and promoting the upregulation of RAGE, which activates the Akt/mTOR/P70S6K and ERK/P90RSK/CREB signaling pathways to regulate GC cell proliferation and migration ( 165 ). In addition, another study showed that the HMGB1/TLR4/MyD88 signaling pathway promotes GC progression and that silencing HMGB1/TLR4/MyD88 signaling in GC cells with HMGB1 siRNA significantly inhibits GC cell proliferation, migration and invasion and induces apoptosis via the NF-κB pathway ( 86 ).…”
Section: The Expression Pattern and Functional Role Of Hmgb1 In The S...mentioning
confidence: 99%